2016
DOI: 10.1002/hed.24499
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parathyroidectomy for primary hyperparathyroidism on quality of life: A case‐control study using Short Form Health Survey 36

Abstract: QOL was significantly lower in patients with untreated PHPT. Surgical treatment was associated with a significant increase in QOL. Decreased QOL should also be considered as an indicator for surgical treatment in patients with PHPT. © 2016 Wiley Periodicals, Inc. Head Neck 38:1213-1220, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Numerous observational studies have evaluated the effect of PTX in PHPT using the SF‐36 survey as well as other non‐disease‐specific questionnaires, suggesting improvement in HRQoL . An observational study by Rolighed et al HRQoL, assessed by SF‐36, were reduced in all 8 domains compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous observational studies have evaluated the effect of PTX in PHPT using the SF‐36 survey as well as other non‐disease‐specific questionnaires, suggesting improvement in HRQoL . An observational study by Rolighed et al HRQoL, assessed by SF‐36, were reduced in all 8 domains compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, these nonspecific symptoms are difficult to quantify, and it is unclear to what extent these symptoms are related to PHPT and whether parathyroidectomy (PTX) relieves the symptoms. Most studies, so far, have evaluated health‐related quality of life (HRQoL) in PHPT using non‐disease‐specific questionnaire such as the Short Form‐36 (SF‐36) general health survey . Four randomized clinical trials (RCTs) assessed HRQoL in asymptomatic PHPT patients, including effect of parathyroidectomy (PTX).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially noteworthy, considering that parathyroidectomy is a cost-effective cure associated with substantial improvement in symptoms. 9 , 12 , 31 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the effect of PTx on patients with PHPT has been evaluated using non-disease specific questionnaires such as the SF-36 and many other HRQoL questionnaires [19][20][21][22][23][24][25][26][27][28]. Rolighed et al [29] reported that HRQoL as assessed using the SF-36 was low in all 8 areas compared with a healthy control group.…”
Section: Discussionmentioning
confidence: 99%